Long-term follow-up of survivors of a first acute coronary syndrome: Results from the French MONICA registries from 2009 to 2017. (1st May 2023) - Gauthier, Victoria; Lafrance, Martin; Barthoulot, Maël; Rousselet, Louis; Montaye, Michèle; Ferrières, Jean; Huo Yung Kai, Samantha; Biasch, Katia; Moitry, Marie; Amouyel, Philippe; Dallongeville, Jean; Meirhaeghe, Aline
Abstract: Aim: The objectives of the study were to characterize the long-term risk of first recurrence of acute coronary syndrome (ACS) among survivors of an incident ACS, as a function of the STEMI/NSTEMI/UA diagnosis. Methods: Men and women (aged 35–74) hospitalized between 2009 and 2016 for an incident ACS in the French MONICA registries and still alive on discharge were followed-up until December 2017. Recurrent events were defined as the first (non-fatal or fatal) ACS occurring after hospital discharge from the incident event. Results: The study comprised 15, 739 incident ACSs with 63, 777 patient-years of follow-up. The cumulative probability [95% confidence interval] of recurrent ACS was 6.7% [6.3–7.1%] at 1 year and 18.4% [17.4–19.5%] at 9 years. The cumulative probability of fatal recurrent ACS was 1.4% [1.2–1.5%] at 1 year and 4.3% [3.6–4.9%] at 9 years. The risk of recurrence did not depend on the type of the incident ACS after adjustment for confounding factors. The most frequent forms of recurrence were NSTEMI and UA. The presence of a major complication (OR = 1.59) and an impaired left ventricular ejection fraction (LVEF) (OR > 1.26) increased the risk of recurrence. The annual 1-year recurrence rates decreased from 7.4% in 2009 to 4.0% in 2016 ( p < 0.001). Conclusion: The recurrence rate after an incident ACS remained high in France, and the risk of recurrence did not depend on the etiology of the first event. Our results emphasize the importance of targeting patients with a major complication and/or an impaired LVEF who are at a higher risk of recurrence. Highlights: The risk of recurrence after an incident acute coronary syndrome did not depend on the etiology of the incident event. The most frequent forms of recurrence are NSTEMI events (after an incident STEMI or NSTEMI) or UA (after an incident UA). The presence of a major complication and an impaired left ventricular ejection fraction increased the risks of recurrence.